KOMPOR HEMAT ENERGI MENGGUNAKAN OLI BEKAS SEBAGAI BAHAN BAKAR - Kurniawan, Irwan; Setyawan, Reinaldi Teguh (POLITEKNIK NEGERI BENGKALIS, 2023)
An energy-efficient stove powered by used oil is an innovative solution designed to reduce dependence on conventional fossil fuels and utilize unused oil waste. This research concentrates on the creation of an efficient stove system that utilizes used oil as its primary energy source. This stove's specific design ensures optimal combustion, minimizes harmful emissions, and enhances heat efficiency. We employ an integrated heating method to maximize energy output, utilizing heat-resistant material construction and a controlled airflow system. We conducted testing of the stove under various operational conditions to measure its performance, temperature stability, and fuel consumption. The results of the experiment show that this stove not only produces stable heat but also has a higher efficiency level compared to traditional stoves. The implementation of this technology is expected to provide an economical and environmentally friendly energy alternative as well as serve as a sustainable solution in the management of used oil waste.